Projection of communicative interaction as a component of assessment and control strategies in teaching languages at university - Liubashenko, Olesia (ScienceRise: Pedagogical Education, 2017)
In the article are demonstrated the results of the study of conditions and possibilities of realization of the project of communicative interaction between students and teachers in the strategy of control and assessment of teaching language. The conclusion was made that the neglect of projection of communicative algorithms and procedures results in the incomplete taking into account of factors of qualitative and correct final exam on language. That is why the possibilities of feedback of study participants, language cognition, experience of speaking in communicative situations, initiative dialog and language partnership are lost. The author assumes that the projection of communicative interaction in the control and assessment strategy essentially and positively influences the check-up and development of language knowledge and speaking skills of students at an exam. The main observation was realized with the involvement of students of engineer and philological specialties of Ukrainian universities, who pass exams in English. It was elucidated that a condition of a successful exam is changes and correction of the perceptive image of communicative interaction between students and teachers at the final control. Statements about necessary changes in the project of communication between a teacher and a student became a conclusion of the research. These changes relate to: features and role of a question at an exam, put by a teacher to a student and vice versa; speaking roles and stereotype genres of teacher’s and student’s speaking; initiative in a dialog; mistakes in speaking at a speaking exam. The author of this article offers the bloc of operations for the activity project that positively influence the perceptive image of an exam in teachers and students. The correct perceptive image of an exam gives a possibility to create communicative situations of the full value communication between teachers and students. Speaking in these situations must become an object of the final control of language knowledge and speaking skills and enrich the experience of participants of an exam by new models of communicative interaction